Atoh1 is required for the formation of lateral line electroreceptors and hair cells, whereas FoxG1 represses an electrosensory fate - Minařík, Martin; Campbell, Alexander S; Franěk, Roman; Vazačová, Michaela; Havelka, Miloš; Gela, David; Pšenička, Martin; Baker, Clare V H (eLife, 2025)
In electroreceptive jawed fishes and amphibians, individual lateral line placodes form lines of neuromasts on the head containing mechanosensory hair cells, flanked by fields of ampullary organs containing electroreceptors-modified hair cells that respond to weak electric fields. Extensively shared gene expression between neuromasts and ampullary organs suggests that conserved molecular mechanisms are involved in their development, but a few transcription factor genes are restricted either to the developing electrosensory or mechanosensory lateral line. Here, we used CRISPR/Cas9-mediated mutagenesis in G0-injected sterlet embryos (Acipenser ruthenus, a sturgeon) to test the function of three such genes. We found that the 'hair cell' transcription factor gene Atoh1 is required for both hair cell and electroreceptor differentiation in sterlet, and for Pou4f3 and Gfi1 expression in both neuromasts and ampullary organs. These data support the conservation of developmental mechanisms between hair cells and electroreceptors. Targeting ampullary organ-restricted Neurod4 did not yield any phenotype, potentially owing to redundancy with other Neurod genes that we found to be expressed in sterlet ampullary organs. After targeting mechanosensory-restricted Foxg1, ampullary organs formed within neuromast lines, suggesting that FoxG1 normally represses their development, whether directly or indirectly. We speculate that electrosensory organs may be the 'default' developmental fate of lateral line primordia in electroreceptive vertebrates.
Keywords: transkripční faktory bHLH; Acipenser ruthenus; rybí proteiny; lateral line; forkhead transkripční faktory; vláskové buňky; vývojová regulace genové exprese; developmental biology; Atoh1; Basic Helix-Loop-Helix Transcription Factors; Gene Expression Regulation, Developmental; buněčná diferenciace; Fish Proteins; Forkhead Transcription Factors; ampullary organs; Foxg1; ryby; sterlet sturgeon; Fishes; Animals; Hair Cells, Auditory; neuromasts; zvířata; proudový orgán; Cell Differentiation; Lateral Line System